FAMILIA Y OIKOS. UN ESTUDIO PUNTUAL SOBRE LA COMPOSICIÓN SOCIO-ECONÓMICA DE LAS PRIMITIVAS COMUNIDADES CRISTIANAS - Fernández Uriel, Pilar; Vidal Manzanares, César (Antigüedad y Cristianismo, 1995)
This is a study of the social and economic composition of the first Christian communities. Analyzing mainly the members of these communities, narned in the sources as heads of Oikos and Familia, owners of goods and house. This investigation helps the study of the social and administrative organization of the institutional, social and ideological events, which vary according to the historical circumstances. These events contribute to the formation of the social reality, the development of which shows us the fundamental importante of the transrnission of the knowlege of History, esencial for the definition of the social and national entities from the nineteenth century on. (...)